Emerging roles of extracellular vesicles in neurodegenerative disorders: focus on HIV-associated neurological complications - Hu, Guoku (Cell Death Dis, 2016)
Exosomes are membrane-enriched extracellular vesicles with a proposed diameter in the range of 30–100 nm. They are released during both normal homeostasis as well as under pathological conditions by most cell types. In recent years, there has been robust interest in the study of these vesicles as conduits for the delivery of information between cells in both analogous as well as disparate tissues. Their ability to transport specialized cargo including signaling mediators, proteins, messenger RNA and miRNAs characterizes these vesicles as primary facilitators of cell-to-cell communication and regulation. Exosomes have also been demonstrated to have important roles in the field of cancer biology and metastasis. More recently, their role in several neurodegenerative disorders has been gaining increased momentum as these particles have been shown to promote the spread of toxic factors such as amyloid beta and prions, adding further validity to their role as important regulators of disease pathogenesis. This review briefly summarizes current findings and thoughts on exosome biology in the context of neurodegenerative disorders and the manipulation of these particles for the development of potential therapeutic strategies.